Op zoek naar een adequate crematieliturgie - Mulder, André (Jaarboek voor liturgieonderzoek, 1992)
This article raises some fundamental questions about the liturgy of cremation. As several sociological investigations point out that belief in an afterlife among catholics is shrinking, and that for the remaining believers their views about this afterlife do not necessarily reflect christian views, a tension is imaginable in liturgical praxis. The Roman burial rite places the Eastermystery of Christ in the centre of the attention, does not symbolise modern theological perspectives on death and resurrection, and pays little attention to the possibility of the presence of unchurched participants. A second problem is that of the deritualisation of our society and the disappearance of death in daily life. How can we produce a ritual of cremation that really functions as a rite of passage? Research on cremation in Great-Britain points out that attention has to be paid to the differences between burial and cremation. Burial symbols cannot without damage be used in the rite of cremation. Cremation demands its own symbols and theology. In the Netherlands therefore a start has been made with further explorative research on the reception of the liturgy of cremation, to come to a clear description of the problems involved and to make a start with the renewal of the Roman Catholic rite of cremation.